THE AFRICAN TRANSFORMATIVE NOTION OF UBUNTU AND THE ENDURANCE OF THE ROMAN QUASI-CONTRACT OF NEGOTIORUM GESTIO WITHIN THE SOUTH AFRICAN CONSTITUTIONAL DISPENSATION (The Pretoria Student Law Review, 2021)
This article serves as a focused discourse on the endurance of the Roman quasi-contract of negotiorum gestio in South African law, so as to establish whether or not this particular rule has been abrogated by disuse and whether, in view of the African transformative notion of ubuntu, it is upheld by the Constitution. I will firstly provide a brief definition and practical operation of the quasi-contract. Secondly, I will discuss whether negotiorum gestio has been abrogated by disuse, with a brief analysis of the doctrine of abrogation. And lastly, I will discuss the constitutional validity of negotiorum gestio, in light of the African transformative notion of ubuntu, including antithetical views on the validity of the quasi-contract.
Keywords: Roman quasi-contract; negotiorum gestio; South African law; abrogated by disuse; ubuntu; the Constitution